Variation Among Species and Populations, and Carry-Over Effects of Winter Exposure on Mercury Accumulation in Small Petrels - Quillfeldt, Petra; Cherel, Yves; Navarro, Joan; Phillips, Richard A.; Masello, Juan F.; Suazo, Cristián G.; Delord, Karine; Bustamante, Paco (Frontiers in Ecology and Evolution, 2022)
Even in areas as remote as the Southern Ocean, marine organisms are exposed to contaminants that arrive through long-range atmospheric transport, such as mercury (Hg), a highly toxic metal. In previous studies in the Southern Ocean, inter-specific differences in Hg contamination in seabirds was generally related to their distribution and trophic position. However, the Blue Petrel (Halobaena caerulea) was a notable exception among small seabirds, with higher Hg levels than expected. In this study, we compared the Hg contamination of Blue Petrels and Thin-billed Prions (Pachyptila belcheri), which both spend the non-breeding season in polar waters, with that of Antarctic Prions (Pachyptila desolata), which spend the winter in subtropical waters. We collected body feathers and blood samples, representing exposure during different time-frames. Hg concentrations in feathers, which reflect contamination throughout the annual cycle, were related to δ13C values, and varied with ocean basin and species. Blue Petrels from breeding colonies in the southeast Pacific Ocean had much higher feather Hg concentrations than expected after accounting for latitude and their low trophic positions. Both Hg concentrations and δ15N in blood samples of Blue Petrels were much lower at the end than at the start of the breeding period, indicating a marked decline in Hg contamination and trophic positions, and the carry-over of Hg burdens between the wintering and breeding periods. Elevated Hg levels may reflect greater reliance on myctophids or foraging in sea-ice environments. Our study underlines that carry-over of Hg concentrations in prey consumed in winter may determine body Hg burdens well into the breeding season.